A study of the performance of organometal trihalide perovskite solar cell due to defects in bulk CH3NH3PbI3 (MAPI) perovskite layer - Adihetty, N. L.; Attygalle, M.L.C.; Narayan, N.S.; Jha, P.K. (Faculty of Graduate Studies , University of Sri Jayewardenepura, 2021)
In this numerical simulation research, we have investigated device performances of p-i-n type organometal trihalide perovskite solar cell by introducing deep and shallow defects in the bulk halide perovskite layer. The organometal halide perovskite solar cell device structure has Glass/ITO/PEDOT:PSS/Bulk-MAPI/2D-MAPI/PCBM/Ag. The open-circuit voltage of the solar cell was decreased due to both shallow and deep defects of the bulk-MAPI layer which increase the recombination of electron-hole pairs in the solar cell. The dark saturation current, which causes to reduce the open-circuit voltage of the solar cell, was increased due to the deep defects in the bulkMAPI layer. Therefore, the power conversion efficiency of the solar cell can be enhanced by minimizing the deep defects in the bulk-MAPI layer, which can increase the open-circuit voltage of the solar cell by suppressing the effect of dark saturation current. We have verified that ShockleyRead-Hall (SRH) recombination is the most predominant recombination mechanism when only the deep defects are presented in the bulk-MAPI layer. Also, this investigation has proved, that Radiative recombination has become the most predominant recombination mechanism when the shallow defects are presented in the bulk-MAPI layer by completely omitting the deep defects of the bulk-MAPI layer. Finally, our model verified that the dark saturation current of the solar cell controls the open-circuit voltage when the recombination is occurring in the solar cell. Iodine interstitial defects that mainly act as deep defects in the bulk-MAPI layer should be minimized to increase the overall solar cell performance and power conversion efficiency of the organometal trihalide perovskite solar cell device
Keywords: Perovskite-Based Solar Cell, Recombination, Dark Saturation Current, Defects, Power-Conversion Efficiency